Uncertain Precision and Price Reactions to Information. - Subramanyam, K.R. (The Accounting Review, 1996)
Presents a stylized model of the effect of information on security prices when there is uncertainty regarding the precision of information. Uncertain precision; Rational expectation models; Earnings-returns relation; Nonlinearity.